Preferensi konsumen terhadap konsumsi â€œrageyâ€ di Kota Manado - Dama, S G; Pangemanan, S P; Kalangi, J K. J; Makalew, A (ZOOTEC, 2021)
CONSUMER PREFERENCES TOWARDS RAGEY CONSUMPTION IN MANADO CITY.This study aims to determine consumer preferences and attributes that are considered consumers of ragey in Manado City. This research was conducted in Manado City, North Sulawesi Province. The location determination was carried out deliberately (purposive sampling) at three restaurants selling ragey, namely the ragey restaurant Tanta Olla, the ragey Roy restaurant and the ragey 21 Telling restaurant from 08 July to 08 August 2019. The research method is survey and interview methods using a questionnaire that has been provided. Samples were determined by accidental sampling with 100 samples. Types of data are primary data and secondary data as well as descriptive analysis and conjoint analysis. The results showed thatÂ  ragey atributs such asÂ  price with a value of 0.530 ,Â  size with a value of 0.410 and proportionÂ  of meat with a value of 0.700 had significant correlation (P<0,05)Â  with consumers preferences. Attributes that are considered by consumers in buying ragey sequentially, namely the proportion of 34.808%, size 33.896% and price of 31.296%.Â